A mechanistic model for wall heat flux partitioning based on bubble dynamics during subcooled flow boiling. (August 2021) - Zhou, Pei; Hua, Shiyang; Gao, Cai; Sun, Dongfang; Huang, Ronghua
Highlights: A mechanistic model for wall heat flux partitioning was developed. An evaporation model for subcooled flow boiling was developed. A modified transient quenching heat transfer model was developed. A bubble sliding heat transfer model was modified. Abstract: This paper aimed to develop a mechanistic model for wall heat flux partitioning based on bubble dynamics in horizontal subcooled flow boiling. The model was established from two dimensions of space and time. In the space dimension, the heating surface was divided into three regions based on the motion characteristics of bubbles, including bubble nucleation region, bubble sliding region, and non-boiling region. In the time dimension, the heat transfer mechanism on the heating surface of the bubble nucleation region and bubble sliding region could be divided into evaporation, condensation, and transient heat transfer. An evaporation model for subcooled boiling was developed based on condensation at the top of the bubble. A transient quench heat transfer model for subcooled flow boiling was modified. The heat flux of each region was obtained by the sum of the time-averaged heat fluxes of these heat transfer mechanisms during a bubble periodic time. The total wall heat flux was obtained by the sum of the area weights of the heat fluxes in these three regions. The new wall heat flux partitioning model and the RPI model were used to predict the experimental values at a variety of flow conditions. The results showed that the new model could well predict the experimental values and the deviation between the predicted heat flux and the experimental results was within 25%. The study also found that it was necessary to consider the condensation at the top of the bubble and the heat transfer mechanism caused by bubble sliding.